Malkaralı Nev’i Yahya’nın “Keşfü’L-Hicâb an Vechi’L-Kitâb” adlı eserinin metin ve incelenmesi 1a-219b yaprakları arası - Telek, Serap (My University, 2010)
XVI. yy. da âlim bir şâir olan Malkaralı Nev’î Yahyâ tarafından kaleme alınmış Keşfü’l-Hicâb an vechi’l-Kitâb, İbn Arabî’nin Fusûsu’l-Hikem isimli eserinin Türkçe tercüme ve şerhidir. Keşfü’l-Hicâb’ın yazılışı, dönemin pâdişâhı III. Murad emriyle gerçekleşmiş ve eser sultan tarafından isimlendirilmiştir. İncelemiş olduğumuz şerh, bilhassa şairlik vasfıyla bilinen Nev’î Efendi’nin “eserlerinin en muazzamı” kabûl edilerek onun ilmî ve tasavvufî yönüne ışık tutmakta, dönemin tasavvufî bakış açısını ortaya koyarken Osmanlı düşüncesinde Ekberî ekolün te’sirlerine bir misâl teşkil etmektedir. Tezimizde Nev’î Efendi’nin şerhinin ilk yarısı günümüz Türkçesine çevrilmiş, Keşfü’l-Hicâb merkezli “İnsân-ı Kâmil ve Rü’yâ” kavramları incelenmiştir. Nev’î Yahyâ, Keşfü’l-Hicâb, İbn Arabî, Fusûsu’l-Hikem

Keşfü’l-Hicâb an Vechi’l-Kitâb, which was written by 16th century’s scholarly poet Nev’î Yahyâ from Malkara, is the translation and annotation of İbn Arabî’s work called Fusûsu’l-Hikem. Keşfü’l-Hicâb was written by order of Murad the Third who was the Sultan of the period and named by him as well. The annotation we have examined, that is acknowledged as the most prodigious work of Nev’î Efendi who is particularly known with feature of poetry, is enlightening his scholarly and Sufistic aspect, while presenting the period’s mystical point of view, constitutes a model for impact of Ekberî School in Ottoman thought. In our thesis, first half of Nev’î Efendi’s annotation has been translated and based on Keşfü’l-Hicâb, consept of “Perfect Human Being (İnsân-ı Kâmil) and Dreams” has been examined. Key Words: Nev’î Yahyâ, Keşfü’l-Hicâb, İbn Arabî, Fusûsu’l-Hikem
Keywords: İslam Dini; Tasavvuf